Levels of awareness, negative attitudes and stigma towards addictions of university students using smoking, alcohol, or substances - Ünal Demir, Figen; Akpınar Aslan, Esma; Batmaz, Sedat; Çelikbaş, Zekiye; Hızlı Sayar, Gökben; Ünübol, Hüseyin (Journal of Dependence, 2022)
Objective: The current study aimed to investigate the psychological distress levels of university students according to their tobacco, alcohol or other substance use and their awareness, negative attitude and stigmatization levels about addiction.Method: 612 students were included in this study and they completed an online questionnaire consisting of the Sociodemographic Data Form, the Three-Dimensional Awareness for Addiction, Attitude and Stigma Scale, the Fagerström Test for Nicotine Dependence, the Alcohol Use Disorders Identification Test, the Drug Abuse Screening Test and the Depression Anxiety Stress 21 Scale.Results: In our study, significantly higher stress, anxiety, depression scores, and lower awareness, negative attitude, stigmatization scores were determined in smokers than nonsmokers. Significantly higher anxiety scores, and lower awareness, negative attitude scores were found in alcohol or substance users than non-users. While there was a positive correlation between awareness and negative attitude, stigma, and smoking scores, there was a negative correlation between awareness and anxiety and alcohol use scores. A positive correlation was found between alcohol use scores and anxiety, depression, stress, and nicotine use scores.Conclusion: Alcohol and substance use are often accompanied by psychiatric symptoms and this should be considered in clinical evaluation. Interventions for improving awareness about addiction, especially in young individuals who are at risk for addiction, may be protective against addiction.
Keywords: Addiction; awareness; attitude; stigma